Educational perspectives in the Caribbean - Keller, Carol (1979)
This paper seeks to examine the relationship between education and those values that are consistently espoused and publicly appealed to by policy makers, intellectuals, and other recognized spokesmen through the various media and, more indirectly, to see how the outlook on education might have been influenced by the unconscious motives of this very group of leaders. It considers: 1) the formulation of goals of education and the relationship between these and the concept of development, 2) the relationship between education and work, and 3) the way in which the international system has affected thinking about the organization of education in the Caribbean
Keywords: Education and development